Impact of Timed Artificial Insemination within Presynchronization Protocol on Reproductive Performance in Dairy Cows - alqaisi, mahmood; Ismaeel Saad Kuridi , Ismaeel Saad Kuridi; Omar Jassim Alhayany , Omar Jassim Alhayany; Ahmed Ibrahem Alsuwaidawi , Ahmed Ibrahem Alsuwaidawi (University of Thi-Qar Journal of agricultural research, 2025)
The aims of this study were to compare of some reproductive performance after timed artificial insemination (TAI) or using artificial insemination (AI) at oestrus detected. Fifty anoestrus cows, selected between 75 and 100 days postpartum, were separated into two equal groups. The control group (n = 25) consisted of cows that received no treatment and underwent artificial insemination when the first postpartum oestrus was identified. The treated group (n = 25) of cows underwent the presynchronization protocol [Day 0 (GnRH); Day 7 (GnRH); Day 14 (PGF2α); Day 15 (PGF2α); Day 16 (GnRH); TAI 16-24 hours latter]. Trans-rectal ultrasonography confirmed the pregnancy on days 35-40 after insemination. The results of this study show pregnancy rate (PR) for the treated group was significantly higher than (P=0.04) to that of the control group (56% vs. 28%, respectively). Furthermore, mean days of days open (DO) and calving interval (CI) for the treated group (104 ±2.8 and 384 ±2.8, respectively) were significantly (P=0.001) shorter than those in the control group 156 ±17.3 and 436 ±17.3, respectively). In conclusion, using TAI within presynchronization protocol eliminate the requirement for oestrus detection and improve reproductive performance at first service in postpartum dairy cows.